Komunikasi Politik: Pertarungan Kepentingan Pemerintah Pusat Dan Pemerintah Daerah Dalam Menangani Covid-19 - Nadia Febiana (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
The covid-19 pandemic finally conquered most of the world's countries. It is uncertain when this pandemic will end. So, it raises public concern as a result of this situation. In addition, the government needs special attention in addressing the covid-19 outbreak of the plague. This article analyzed government political communications in the case of covid-19. The research methods used are qualitative methods using literary studies and reflect classic communication theories. The study was to learn the political communication between the local government and the central government in dealing with the covid-19 pandemic. There is a custom-centered, mentor-relationship disc in responding to this worldwide problem. In today's situation the role of government is critical to address it. In reality, though, governments are not prepared to deal with this. Miscommunication between local and central governments is often found and there is a overlap in policy and a mix of information that would then generate public distrust of the government. The study has concluded that poor government political communications and intergovernmental and inter-governmental relations related to covid-19 management in Indonesia. This requires improving the government's political communications to prevent public uproar.